The Jurisprudence of Tolerance a study on Transmission and Vision - Laklimi, Ahmed Al-Madani; Choubed, Norddine; Raki, Abdelhamid; Agli, Mustafa (Journal of Ecohumanism, 2024)
This study attempts to resolve two jurisprudential issues, the first one is objective, and the second is methodological. The objective issue is linked to the atrophy of the tolerance concept in the jurisprudential heritage. That is, in the books of general jurisprudence or the collections of calamities, as indicated by the jurisprudential laws of the subject of "Jihad" in both sources. While the second one appears in the illusion that the approach of principles of jurisprudence can produce only inherited jurisprudence in which tolerance does not seem to have any effect. This research has adopted a critical and analytical approach to resolving the first issue. In contrast, it has adopted a constructive and structural one for the second issue, as indicated by the proposed title with the terms: "transmission" and "vision".